Impact of Rain Snow Threshold Temperature on Snow Depth Simulation in Land Surface and Regional Atmospheric Models - 文莉娟 Nidhi NAGABHATLA 吕世华 Shih-Yu WANG (Advances in atmospheric sciences, 2013)
This study investigates the impact of rain snow threshold （RST） temperatures on snow depth simulation using the Community Land Model （CLM） and the Weather Research and Forecasting model （WRF--coupled with the CLM and hereafter referred to as WRF_CLM）, and the difference in impacts. Simulations were performed from 17 December 1994 to 30 May 1995 in the French Alps. Results showed that both the CLM and the WRF_CLM were able to represent a fair simulation of snow depth with actual terrain height and 2.5~C RST temperature. When six RST methods were applied to the simulation using WRF_CLM, the simulated snow depth was the closest to observations using 2.5~C RST temperature, followed by that with Pipes＇, USACE, Kienzle＇s, Dai＇s, and 0~C RST temperature methods. In the case of using CLM, simulated snow depth was the closest to the observation with Dai＇s method, followed by with USACE, Pipes＇, 2.5~C RST temperature, Kienzle＇s, and 0~C RST temperature method. The snow depth simulation using the WRF_CLM was comparatively sensitive to changes in RST temperatures, because the RST temperature was not only the factor to partition snow and rainfall. In addition, the simulated snow related to RST temperature could induce a significant feedback by influencing the meteorological variables forcing the land surface model in WRF_CLM. In comparison, the above variables did not change with changes in RST in CLM. Impacts of RST temperatures on snow depth simulation could also be influenced by the patterns of temperature and precipitation, spatial resolution, and input terrain heights.